Modelling and performance evaluation of sustainable arresting gear energy recovery system for commercial aircraft - Deja, Jakub; Dayyani, Iman; Skote, Martin (Taylor & Francis, 2022)
A significant amount of kinetic energy is dissipated during each commercial aircraft landing. To improve energy efficiency and environmental sustainability, the kinetic energy can instead be converted to electricity by utilizing the arresting gear systems. This paper presents a novel design that couples an arresting gear system to electrical generators. The results show that the system can successfully recover aircraft kinetic energy and is applicable to different aircraft sizes ranging from Airbus A319 up to A380. Beyond system performance, wider context technical aspects including system integration into grid with multiple energy storage possibilities, safety and passenger comfort are discussed.
Keywords: commercial aircraft; kinetic energy recovery; arresting gear; landing phase